Hubungan Antara Kebiasaan Makan Pagi Dan Status Gizi Dengan Tingkat Kesegaran Jasmani Pada Siswi Di Pondok Madrasah Aliyah Al - Manshur Tegalgondo, Klaten - ZULIAN, Sika Nurindah; , Rusdiyanto, SKM., M.Si; , Muwakhidah, SKM, M.Kes (2015)
Background : Increased nutrient requirements in adolescents is very important.Food intake is the dominant factor that determines a person's level of physicalfitness which humans need to eat breakfast in the morning due to the expectedoccurrence of the availability of the energy used for the first hour of activity.Based on some of the above opinion, breakfast is very important in order tomaintain the nutritional status and physical fitness.Objective : : To determine the relationship between breakfast habits andnutritional status with physical fitness level of the female students in the cottagedaughter Madrasah Aliyah Al-Mansur Tegalgondo, Klaten.Methods : This study was an observational study with cross sectional method.The sample in this study is a student of class X and XI in cottage MadrasahAliyah Al-Mansur Tegalgondo the number of 51 students. Data collectiontechniques breakfast using 24-hour recall, physical fitness with (TKJI) and measurement of nutritional status with BMI/U. At the student. Data were analyzed using Chi Square test. Results : Schoolgirl in Madrasah Aliyah Al-Mansur Tegalgondo Klaten not have the habit of eating breakfast in the amount of 51.0%. Having a normal nutritional status that is equal to 74.5%. Have physical fitness in the medium category that is equal to 52.9%. Conclusion : There was a significant correlation between eating habits morning with student physical fitness Madrasah Aliyah Al-Mansur Tegalgondo Klaten with the value (p = 0.017). Suggestion : For schools can make cooperation with the health department to further improve eating habits early, especially for girls